Homecare professionals' observation of deteriorating, frail older patients: A mixed‐methods study. Issue 13 (13th April 2020) - Strømme, Torunn; Aase, Karina; Tjoflåt, Ingrid
Abstract: Aim and objectives: To develop knowledge about homecare professionals' observational competence in early recognition of deterioration in frail older patients. Background: The number of frail older patients in homecare has been rising, and these patients are at higher risk of deterioration and mortality. However, studies are scarce on homecare professionals' recognition and response to clinical deterioration in homecare. Design: This study applies an explorative, qualitative, mixed‐methods design. Methods: The data were collected in two homecare districts in 2018 during 62 hr of participant observation, as well as from six focus group interviews. The data were subjected to qualitative content analyses. The Standards for Reporting Qualitative Research (SRQR) checklist was used to report the results. Results: The data analyses revealed two main themes and five sub‐themes related to homecare professionals' observational practices. The first main theme entailed patient‐situated assessment of changes in patients' clinical condition, that is, the homecare professionals' recognised changes in patients' physical and mental conditions. The second theme was the organisational environment, in which planned, practical tasks and collaboration and collegial support were emphasised. Conclusions: The homecare professionals in the two districts varied in their ability to recognise signs of patient deterioration. Their routines are described in detailed work plans, which seemed to affect assessment of their patients' decline. Relevance for clinical practice: The results can inform homecare services on how homecare professionals' observational competence and an appropriate organisational system are essential in ensuring early detection of deterioration in frail older patients.